The AR6 Scenario Explorer and the history of IPCC Scenarios Databases: evolutions and challenges for transparency, pluralism and policy-relevance - Béatrice Cointe (npj Climate Action, 2024)
Abstract Emissions scenarios have always been a crucial part of IPCC reports. They are instrumental to the shared assessment of climate research and to its policy relevance. Since the early days of climate change research, the number of emissions and mitigation scenarios in the literature has grown exponentially. An infrastructure was developed to collect, standardize, and share increasing amounts of scenarios data. The Integrated Assessment Modeling (IAM) community and IIASA have led this work. This infrastructure is central to the work of the IPCC Working Group III, but it also serves to coordinate and disseminate scenarios research. Adopting a socio-historical perspective, this article focuses on the AR6 Scenarios Database as a keystone in this infrastructure and as a site where tensions regarding the role and mandate of the IPCC are play. It retraces the co-evolution of IPCC Scenarios Databases and of the IAM community, and shows how the AR6 Scenarios Database compares and contrasts with previous Scenarios Databases. It then unpacks how ambitions to enhance diversity and transparency in the AR6 Working Group III use of scenarios translated in the design and use of the AR6 database. It analyses the attempt to expand the scope of the database beyond IAMs and discusses the challenges encountered in the process.